Development and Effectiveness of "SAHLA" Interactive Animation Media Based on Ispring Suite 11 to Enhance The Interest and Arabic Language Skills of Madrasah Aliyah Students - Shela Nur Anantasya; Rina Dian Rahmawati (Litteratura: Jurnal Bahasa dan Sastra, 2026)
Arabic language learning, which encompasses the four core skills listening, speaking, reading, and writing, requires interactive and innovative learning media. However, in practice, the learning process is still dominated by conventional methods with limited use of media, resulting in low interest and poor Arabic language skills among female students. This study aims to develop, assess the feasibility of, and test the effectiveness of an interactive animated learning medium based on the Android Smart Arabic Holistic Learning App (SAHLA) developed using iSpring Suite 11 to enhance the interest and Arabic language skills of female students in the 10th grade at the K.H. Abd. Wahab Hasbulloh Bahrul Ulum Tambakberas Jombang Elite Islamic High School. This study employed the Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research instruments included a needs analysis questionnaire, an expert validation sheet, a student response questionnaire, and learning outcome tests in the form of pre-tests and post-tests. The research results show that the media needs level reached 85.4% (very high category), content expert validation was 80% (acceptable category), media expert validation was 94% (very acceptable category), and student response was 87.7% (very good category). The results of the paired-sample t-test showed that the calculated t-value of 39.2 was greater than the critical t-value of 2.032 at a significance level of 0.05. In addition, there was an increase in the mean score from 30.63 (pre-test) to 81.15 (post-test), with an average difference of 38.57. Thus, the SAHLA learning medium is deemed suitable and effective for improving the students’ interest in and proficiency in the Arabic language. Keywords: interactive learning media, SAHLA, iSpring Suite 11, Arabic language skills